Alphabet under construction - Fleming, Denise, 1950- (New York : Holt, 2002)
A mouse works his way through the alphabet as he folds the "F," measures the "M," and rolls the "R."
1.8
K-3
K-3
NP
Keywords: Mice -- Juvenile fiction; Mice -- Fiction; Alphabet; Mice -- Fiction; Alphabet